DEMOGRAFI PENGGUNA PRODUK DIGITAL ASLI KOTA PONTIANAK METODE CROSSTABS - Wenny Pebrianti (Fakultas Ekonomi dan Bisnis, Universitas Papua., 2020)
This study aims to determine the response of Pontianak City people to the original digital products of Pontianak by examining the association based on the category of gender, age, education, occupation, income and frequency of use with cross tabulation method. Research is descriptive research. The population in this study is the people of Pontianak City who have used digital product services from Pontianak, namely Angkuts, Tripy and Gurukite.com. The sample size of 100 respondents was selected by purposive sampling, while the sample criteria were respondents with ages above or equal to 17 years, knew and had used Angkuts, Tripy or Gurukite.com services. Data processing techniques use cross tabulation analysis and association testing with chi square. The results of cross tabulation and chi square between categories of gender, age, education, occupation, income and frequency of use showed significant results. There is a strategic relationship between categorical variables to be followed up by pontianak digital businessmen.